IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Giving Question and Getting Answers cooperative learning model in improving high school students’ critical thinking skills and to identify supporting and inhibiting factors. This study employed a descriptive qualitative method. Data collection involved observation, interviews, and documentation. Data analysis employed an interactive model through data collection, data reduction, presentation, and drawing conclusions. To ensure the accuracy of the data, the researcher employed triangulation techniques. The results of the study indicate that 1) students’ critical thinking skills through the implementation of the cooperative learning model of Learning type Giving Question and Getting Answer are shown by the ability to understand question, analyze, evaluate, conclude, and express opinions logically, although not evenly distributed among all students; 2) supporting factors include encauraging student collaboration, training student responsibility, increating interaction, between students, training in expressing opinions, direction from teachers, student enthuasiasm, and the use of tools that make it easier for students. Meanwhile, inhibiting factors include not all students daring to ask questions or express opinions, differences in understanding of the material, lengthy discussion times, the persistence of students’ lack of participation, and limited learning resources.